The Only Universal Monarchy: Freemasonry, Ritual, and Gender in Revolutionary Rhode Island, 1749-1803 - Biagetti, Samuel (REHMLAC+, Revista de Estudios Históricos de la Masonería Latinoamericana y Caribeña plus, 2015)
The researcher Samuel Biagetti has defended a doctoral thesis, entitled “The Only Universal Monarchy: Freemasonry, Ritual, and Gender in Revolutionary Rhode Island, 1749-1803”, at Columbia University in the United States of America in May, 2015.